The defect evolution in shock loaded tantalum single crystals. (15th April 2018) - Pang, B.; Case, S.; Jones, I.P.; Millett, J.C.F.; Whiteman, G.; Chiu, Y.L.; Bronkhorst, C.A.
Abstract: The defect structures of three different orientation ([001], [011] and [111]) shocked single crystals of tantalum have been characterised using scanning electron microscopy and transmission electron microscopy. The defect evolution and the response of the single crystals are found to be highly dependent on the orientation of the single crystals and the position in the specimen. Crystal plasticity simulation has been used to calculate the strain tensor in the specimens as a function of position and time. The defect types and distributions are analysed in terms of the shock wave and the lateral and back release waves. Twins at the sample centre and front surface were created by the shock wave front. The twins at the back of the sample close to the side surface are produced by the interaction of the release waves. Twinning area fraction and dislocation density are higher at the impact surface region than at the back surface due to decay of the elastic precursor and the difference in loading duration. Twinning acts as a major deformation mechanism and has a strong influence on the Hugoniot elastic limit (HEL) and spall strength when the loading direction is [011] or [111]. Graphical abstract: Image 1